O circuito espacial de produção e os círculos de cooperação da soja no Maranhão no período técnico-científico informacional - Botelho, Raimundo Edson Pinto (2010)
The study in screen it has as objective the understanding of the space circuit of production and the circles of cooperation of the soy that if develop in the Maranhão in the technician-scientific-informational period. Characterized for the material and incorporeal flows if they develop in the Maranhão, from the moment where it had a process of integration of the maranhense territory while peripheral space of the capitalist dynamics, that if gave through the politics of regional integration created by the State, but when it had a process of selective modernization, also partial and conservative of the agriculture, that made possible the significant increase of the production and reproduction of the capital. The study sample that with the advent of the soy, had a concentration of the production techniques, mainly in the agricultural region of Balsas, due to bigger it offers of lands, time of implantation of the culture, technique accumulated in the production, whereas in the agricultural region of Chapadinha, these indices still are without representation. Moreover, the intensification of the agricultural credit, the agrarian politics and tax incentives are elements that have propitiated increase of the production of the soy. The development of the space circuit and circles of cooperation of the soy, a side, create new forces politics in the Maranhão that can result in the creation of a new state, the other, are responsible, for the elimination of part of the subsistence agriculture, producing social problems as, agrarian concentration and unemployment. The study it still evidences the appropriation of the place for a small number of companies that has generated, beyond an intense concentration of income, an alienation of the territory, in view of that this is used for a strange purpose to the place and the yearning of the population does not stop